Cognitive phenomenology - Chudnoff, Elijah (New problems of philosophy, 2015)
"This is the first book to fully address the question of cognitive phenomenology, applying phenomenology to the study of thought itself. Can phenomenology have a cognitive or conceptual character? Is introspection an argument for cognitive phenomenology, or against it? If consciousness is an unbroken "stream" as William James argued, how can it be cognitive? Elijah Chudnoff begins with a brief historical overview of the origins of cognitive phenomenology in the work of phenomenologists such as Brentano and Husserl and later philosophers such as Ryle, Shoemaker and Smart. He then examines the following topics: - phenomenal contrast arguments - introspective awareness - cognitive phenomenology and temporality, including the "stream of consciousness" - cognitive phenomenology and intrinsic value: do some cognitive experiences possess intrinsic value because of their distinctive phenomenology? - intentionality - the relation between cognitive phenomenology and reasoning. Including chapter summaries, annotated further reading, and a glossary, this book is essential reading for anyone seeking a clear and informative introduction to and assessment of cognitive phenomenology, whether philosophy student or advanced researcher. It will also be valuable reading for those in related subjects such as philosophy of mind, philosophy of psychology and epistemology"--